Intrasystemic Contradictions in Punctuation Marks of Appositives and Introductory Words in Ossetian: Causes and Solutions - A. F. Kudzoeva; L. B. Morgoeva (Научный диалог)
The subject of analysis is the punctuation marks of appendices and introductory words in the Ossetian — one of the problematic phenomena in contemporary Ossetian studies. The relevance of the study is determined, firstly, by the absence of works in Ossetian linguistics dedicated to the investigation of punctuation theory issues, and secondly, by the necessity of codifying punctuation norms in the Ossetian. The novelty of the research lies in the attempt to conduct a contrastive analysis of the reasons and circumstances of separating appendices and introductory words in Ossetian and Russian, as well as identifying gaps in Ossetian punctuation. It is demonstrated that actual punctuation practice does not deviate from the established norm in cases where the reasons for separating appendices and introductory words coincide in Ossetian and Russian. Special attention is given to the issues of distinguishing appendices and introductory words in positions that have no analogues in the Russian. The significance of word order and the presence of clitics in a sentence for the correct placement of punctuation marks in complex sentences is demonstrated. The punctuation formatting of appendices that have two qualifying words or a common postposition with a qualifying word is justified. The separation of introductory words that are part of an accentual complex is also commented on.